Informe final de práctica empresarial en el proceso de radicación de cuentas médicas en la IPS Traumas y Fracturas (2022)
The objective of the Business Practice was to acquire abilities and skills in administrative procedures and the strengthening of the occupational health of the officials through mitigation actions of the Sick Building Syndrome that is occurring in the account filing area. To this end, actions such as leadership in active breaks, education and training were implemented to help reduce diseases that have occurred in the area, such as musculoskeletal disorders. In this way, active breaks are an effective instrument to improve the physical condition of workers and their better performance in the workplace.